Desde Martín Cortés hasta Martín Villar: el mestizaje como estigma en La violencia del tiempo de Miguel Gutiérrez Correa - Otero Luque, Frank (2019)
Martín Villar Flórez, a mestizo, decides not to have descendants in order to draw a line under his mixed bloodline, which he considers spurious. Martín’s decision suggests he has internalized the hegemonic discourse that, aiming to legitimize and to protect white people’s privileges, since colonial times used to promote the belief that the white race is superior to the subaltern’s race (i.e. Indians and mestizos). Even though in Peru extreme socioeconomic inequity and the color of the skin no longer go hand-in-hand as they did in the past, La violencia del tiempo should not be read as an anachronistic text of social denunciation, but quite the opposite. Far from ignoring the racial tension intrinsic to the Peruvian society, this novel frontally confronts the fallacious romantic vision that was given to racial mixing as a panacea for the harmonious resolution of socio-cultural conflicts.conflicts.